Radiatul Adawiah KEEFEKTIFAN PENGGUNAAN APLIKASI GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN DI MASA PANDEMI COVID 19 - Radiatul Adawiah (STKIP Paris Barantai, 2021)
The impact of Covid-19 in various aspects of life throughout the region has been disrupted without exception in the fields of education and learning. E-learning can be used to improve understanding of the material and expand the sources of teaching materials as well as add learning activities and assist lecturers in streamlining online learning time. This research is an experimental research with a development stage that produces an e-learning learning by applying the Google Classroom Application as a learning medium. The research was carried out in the mathematics education department of STKIP Paris Barantai in the Spatial Analytical Geometry course. The sample was taken by purposive sampling method, namely from the population of students who attended lectures. The variables studied in this study include aspects of Google classroom learning management which consist of variables, evaluation of the implementation of google classroom learning, design and manufacture of materials, learning planning, learning interactions, and delivery of learning. The results of this study through the use of Google Classroom as a learning medium during the COVID-19 pandemic, it was quite effectively used with a tendency rate of 68.18%.